NEW AND CRITICAL MALAYSIAN PLANTS IV - A. J. G. H. KOSTERMANS (Research Center for Biology, 1956)
1. Sixteen new species are described in Guttiferae : Garcinia longipedicellata, G. segmentata; Kayea laevis, K. paludosa.Lauraceae:Alseodaphne data, A. gigaphylla, A. obovata ; Beilschmiedia argentea, B.dilmyana, B. gigantocarpa,B.kinabaluensis, B. myrmecophila, B. rufolanata,B. rufoperulata,B. wieringae;Dehaasia novoguineensis. 2. Seven new combinations are coined in Lauraceae : Alseodaphne archboldiana (Allen) (basonym : Nothaphoebe archboldiana Allen),A. reticulata (Gamble) (basonym : Nothaphoebe reticulata Gamble) ; Beilschmiedia cuneata (Meissn.) (basonym : Persea cuneata Meissn.) ; Beilschmiedia palembanica (Miq.)(basonym : Cryptocarya palembanica Miq ) ; Dehaasia longipedicellata (Ridley) (basonym :Beilschmiedia longipedicellata Ridley), D. oblanceolata (Merr.) (basonym : Beilschmiedia oblanceolata Merrill) ; D. titanophytta (Airy Shaw) (basonym : Beilschmiedia titanophylla Airy Shaw). 3. Two new names are coined in Lauraceae : Dehaasia membranacea Kosterm. (based on Dehaasia longipedicellata (non Ridley) Merrill).Sterculiaceae : Sterculia perryae Kosterm. (based on Sterculia clemensiae (non Ridley) Merr. & Perry).